Issues on job mobility in restaurant industry: study on salary, work environment and promotions / Noorliza Zainol ... [et al.] - Zainol, Noorliza; Abdullah, Dahlan; Ahmad Rozali, Abdul Rahman; Bahari, Khairil Anuar; Mohd Kamal, Saiful Bahri (Universiti Teknologi MARA, Perlis, 2020)
Employees are known as an asset to an organization where success or failure of an organization as determinant closely to them. According to the Department of Statistics Malaysia (2017), there are 891,616 employees working in restaurants in the year 2015. The statistic also shows that staff mobility drastically increases every year and this scenario has been debated among hospitality players. The focus of this study is to discern about issues of job mobility that occur in the restaurant industry in related to salary, working environment and promotion. The objective are: a) to identify issues in job mobility among workers and b) to investigate whether salary, working environment and promotion become a factor of job mobility among employees. This study used a quantitative method and a distribution of 450 sets of the questionnaire to the target respondents of employees at casual dining restaurants around George Town, Pulau Pinang. Only 385 questionnaires we able to be used for this study, as the rest were not completed. Results showed that salaries, work environment and promotion were closely related to the intention of people to pursue their careers in the restaurant industry.